Production and Consumption of Fuel and Energy Resources in the Western Economic Zone of the Republic of Sakha (Yakutia): Analysis, Assessment and Forecast - ELYAKOVA, Izabella Damdinovna; ELYAKOV, Aleksandr Lvovich; BARAKHOVA, Vera Vasilievna; KHRISTOFOROV, Aleksandr Andreevich; DANILOVA, Larisa Ivanovna; KARATAEVA, Tamara Aleksandrovna; NOEVA, Elena Evgenyevna (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018, 2019)
In this article, we give a comparative assessment of the efficiency of production and consumption of fuel and energy resources in the Western Economic Zone (WEZ) of the Republic of Sakha (Yakutia), following the results of the research work ‘Assessment and the Main Trends in the Change of the Natural and Socio-Economic Status and Human Potential of the Western Economic Zone of the Republic of Sakha (Yakutia)’ within the program of comprehensive scientific research under the state contract N5327 of August 2, 2017. Based on the analysis, we identify the existing risks of fuel and heat supply in the WEZ areas as well as develop recommendations for effective consumption and production of fuel and energy resources in the WEZ areas. The study makes it possible to develop comprehensive recommendations for increasing the efficiency of production and consumption of fuel and energy resources in the WEZ areas.